Poor treatment compliance leads to a higher mutation for rifampicin resistance in multibacillary leprosy patients (Medical Journal of Indonesia, 2018)
Background: Multidrug therapy (MDT) is a safe and effective drug combination for leprosy treatment that can prevent drug resistance. Mycobacterium leprae resistance, especially to rifampicin, is a serious problem as it potentially thwarts the worldwide leprosy-elimination program by the World Health Organization (WHO). One of the suspected causes of rifampicin resistance is poor treatment compliance. It was necessary to assess the association between the treatment compliance and the occurrence of mutation rifampicin resistance in multibacillary (MB) leprosy patients.Methods: A comparative, analytical, cross-sectional study was performed in MB leprosy patients who had completed treatment at the Dermatovenereology Outpatient Clinic in Cipto Mangunkusumo Hospital and the Sitanala Center for Leprosy Hospital from October 2012 to April 2013. Based on treatment regularity and history of drug discontinuation, the subjects were classified as either having good or poor compliance. Skin smear from a slit skin smear (SSS) examination was further analyzed by using the polymerase chain reaction (PCR) sequencing technique to detect rifampicin resistance.Results: Fifty-seven study subjects were enrolled in this study. In the good treatment compliance group (29 subjects), only 1 case of mutation for rifampicin resistance was found. Meanwhile, in the poor drug compliance group (28 subjects), 8 cases of mutation for resistance (29%) were found. This difference in mutation rate was statistically significant (OR=11.2; 95% CI=1.296–96.787; p=0.012).Conclusion: This study revealed that the risk of occurrence of M. leprae resistance to rifampicin in patients with poor drug compliance was significantly higher than in those with good drug compliance.